2023
DOI: 10.3389/fpsyt.2023.1157402
|View full text |Cite
|
Sign up to set email alerts
|

Eating disorder symptoms among children and adolescents in Germany before and after the onset of the COVID-19 pandemic

Abstract: BackgroundDisordered eating is highly prevalent among children and adolescents. Since the outbreak of the COVID-19 pandemic, hospitalizations due to eating disorders have peaked and overweight has risen. The aim of this study was to determine differences in the prevalence of eating disorder symptoms among children and adolescents in Germany before and after the onset of the COVID-19 pandemic and to identify associated factors.Materials and methodsEating disorder symptoms and associated factors were examined in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 103 publications
0
1
0
4
Order By: Relevance
“…In addition, it is suggested that cross-cultural research is needed to determine the consistency and structure of EAT-8 in different geographical contexts of Peru. In addition, it is also relevant to conduct longitudinal studies to identify changes in EAT-8 scores after the state of social confinement because of COVID-19, given that during this period an increase in EBDs could be noted in different contexts (Cerniglia and Cimino, 2023;Napp et al, 2023). It should be noted that the present study was conducted before social isolation, which allowed us to maintain a view on EAT-8 levels prior to that period.…”
Section: Limitationsmentioning
confidence: 95%
“…In addition, it is suggested that cross-cultural research is needed to determine the consistency and structure of EAT-8 in different geographical contexts of Peru. In addition, it is also relevant to conduct longitudinal studies to identify changes in EAT-8 scores after the state of social confinement because of COVID-19, given that during this period an increase in EBDs could be noted in different contexts (Cerniglia and Cimino, 2023;Napp et al, 2023). It should be noted that the present study was conducted before social isolation, which allowed us to maintain a view on EAT-8 levels prior to that period.…”
Section: Limitationsmentioning
confidence: 95%
“…Eine Zunahme von Esstörungen [21] sowie erhöhte Hospitalisierungsraten bei Anorexia Nervosa [22] im Rahmen der Pandemie wurden international beobachtet. Im Kon trast dazu konnte in einer Analyse der COPSY-Studie (COVID-19 and Psychological Health) eineReduktion von Esstörungs-Symptomen bei Mädchen während der COVID-19-Pandemie beobachtet werden, während in der männlichen Gruppe das Risiko anstieg [23]. Lockdowns scheinen insgesamt einen negativen Effekt auf die Gesundheit zu haben.…”
Section: Diskussionunclassified
“…Isso pois problemas relacionados à saúde mental na faixa pediátrica promovem maior risco de desenvolvimento de outros transtornos mentais na vida adulta. Entre os distúrbios emocionais envolvendo a pandemia estão a depressão, ansiedade, sintomas relacionados ao trauma e desenvolvimento ou exacerbação de sintomas relacionados a transtornos alimentares (TAs) (NAPP et al;SERUR et al;.…”
Section: Introductionunclassified
“…No mesmo viés, outros problemas se tornaram ainda mais evidentes, como é o caso dos TAs. O aumento desses se deram em virtude da perda de fatores de proteção e aumento dos elementos de risco na rotina de crianças e adolescentes (KATZMAN;NAPP et al;2021;.…”
Section: Introductionunclassified
See 1 more Smart Citation